Bagaimana Masyarakat Memandang Seseorang Berdasarkan Kekayaan dan Gender Mereka dalam Novel Persuassion Karya Jane Austen - Syadri, Faizah Izzati (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2024)
This study focuses on the discussion of the novel Persuasion, written by Jane Austen and published in 1817. This novel tells the story of Anne Elliot, whose family and godmother persuaded her to break off her engagement with Captain Wentworth because he is not a noble nor has wealth, which is why he is not suitable for Anne, who is a noble. The social class in the Regency period affected the upper class and the lower class, whether in economy, wealth, or social standing. The author uses a Historical biographical approach to relate the period and the author's life with the novel. The author uses a qualitative method to describe the findings. At the end of the study, the author finds that (1) The upper class had many scandals and did not care about the problems of the lower class, and (2) Marriage is considered to maintain the economy and social stability for women. (3) Naval soldiers were treated politely after gaining wealth and social status. (4) Austen's life and values influence the plot and character of the novel. The findings conclude that the novel Persuasion reflects how society in the Regency period saw people by their wealth and gender.